Risk factors for poor prognosis in children and adolescents with COVID-19: A systematic review and meta-analysis. (November 2021) - Shi, Qianling; Wang, Zijun; Liu, Jiao; Wang, Xingmei; Zhou, Qi; Li, Qinyuan; Yu, Yang; Luo, Zhengxiu; Liu, Enmei; Chen, Yaolong; ,
Abstract: Background: This study provides the first systematic review and meta-analysis to identify the predictors of unfavorable prognosis of COVID-19 in children and adolescents. Methods: We searched literature databases until July 2021 for studies that investigated risk factors for unfavorable prognosis of children and adolescents with COVID-19. We used random-effects models to estimate the effect size with 95% confidence interval ( CI ). Findings: We identified 56 studies comprising 79, 104 individuals. Mortality was higher in patients with multisystem inflammatory syndrome (MIS-C) (odds ratio [ OR ]=58.00, 95% CI 6.39–526.79) and who were admitted to intensive care ( OR =12.64, 95% CI 3.42–46.68). Acute respiratry distress syndrme (ARDS) ( OR =29.54, 95% CI 12.69–68.78) and acute kidney injury (AKI) ( OR =55.02, 95% CI 6.26–483.35) increased the odds to be admitted to intensive care; shortness of breath ( OR =16.96, 95% CI 7.66–37.51) increased the need of respiratory support; and neurological diseases ( OR =5.16, 95% CI 2.30–11.60), C-reactive protein (CRP) level ≥80 mg/L ( OR =11.70, 95% CI 4.37–31.37) and D-dimer level ≥0.5ug/mL ( OR =20.40, 95% CI 1.76–236.44) increased the odds of progression to severe or critical disease. Interpretation: Congenital heart disease, chronic pulmonary disease, neurological diseases, obesity, MIS-C, shortness of breath, ARDS, AKI, gastrointestinal symptoms, elevated CRP and D-dimer are associated with unfavourable prognosis in children and adolescents with COVID-19. Funding: None.